On the Christoffel function and classification in data analysis - Lasserre, Jean B. (Comptes Rendus. Mathématique, 2022)
We show that the empirical Christoffel function associated with a cloud of finitely many points sampled from a distribution, can provide a simple tool for supervised classification in data analysis, with good generalization properties.